Platelet-derived Microvesicles in Thrombotic Thrombocytopenic Purpura and Hemolytic Uremic Syndrome - Galli, Monica; Grassi, Anna; Barbui, Tiziano (Thrombosis and Haemostasis, 1996)
Thrombotic thrombocytopenic purpura (TTP) and the related hemolytic uremic syndrome (HUS) are disorders characterized by thrombocytopenia, microangiopathic hemolytic anemia, a variable degree of impairment of renal function and fluctuating neurological symptoms, which are thought to be due to platelet activation and subsequent formation of thrombi in the microcirculation. Since platelet activation is accompanied by the generation of microvesicles (PMPs), we determined their presence in patients with TTP and HUS by flow cytometry. The analysis was performed in whole blood, using FITC-conjugated monoclonal antibodies (CD 42b and/or CD 61a). PMPs were discriminated from platelets on the basis of size and fluorescence profiles. Their levels in 21 normal controls ranged between 2.4% and 9.4% (mean ± SD: 5.2 ± 1.99%). No correlations were found with platelet number. PMPs were then evaluted in 13 patients with TTP and 2 cases of HUS. In all patients they were found higher than in controls, ranging from 11.0 to 91.1% (45.0 ± 26.0%; p = 0.0001 vs controls). PMPs were serially measured in patients with TTP: at diagnosis a correlation between PMPs and platelet number was found (R^2 = 0.669) and the time-course showed that the improvement of both microangiopathy and clinical manifestations of cerebral and renal involvement was accompanied by a progressive normalization of PMP levels and platelet count.PMP levels were measured also in patients suffering from other forms of thrombocytopenia: they were 17 patients with idiopathic thrombocytopenic purpura and 10 patients with acute leukemias and severe thrombocytopenia during the aplastic phase following chemotherapy. PMP ranges were: 2.0−79.6% (21.6 ± 20.8%; p = 0.001 vs controls) and 4.6−12.5% (8.8 ± 2.4%; p = 0.0001 vs controls), respectively. No correlations were found between platelet number and the absolute number of PMPs in these 2 groups of patients.These findings show that increased levels of PMPs may be found in peripheral thrombocytopenias and suggest that their presence may be clinically relevant, particularly in the microangiopathic forms.